Prevalence and incidence of post-traumatic stress disorder and symptoms in people with chronic somatic diseases: A systematic review and meta-analysis - Lunkenheimer, Frederike; Garatva, Patricia; Steubl, Lena; Baumeister, Harald (Frontiers in Psychiatry, 2023)
Introduction Comprehensive evidence on prevalence and incidence of post-traumatic stress disorder (PTSD) and symptoms (PTSS) in people with chronic somatic diseases (CD) is lacking. Objective To systematically and meta-analytically examine prevalence and incidence of PTSD and PTSS in people with CD compared with people without CD. Methods MEDLINE, Embase, and PsycINFO were searched from inception (1946) to June 2020. Studies reporting point, 12-month, lifetime prevalence, or 12-month incidence of PTSD and PTSS in people with CD were selected and reviewed in accordance with PRISMA guidelines by two independent reviewers. Risk of bias was assessed by a combination of the Newcastle-Ottawa Scale and recommendations of the Cochrane Collaboration for non-comparative studies. Pooled estimates were calculated using random effects meta-analyses. Between-study heterogeneity was assessed using the I2 statistic. Results Data were extracted from studies reporting on point prevalence (k = 60; n = 21,213), 12-month prevalence (k = 3; n = 913), and lifetime prevalence (k = 6; n = 826). 12-month incidence estimates were not available. The pooled estimate for the point prevalence of PTSD (k = 41) across CD was 12.7% (95% CI, 8.6 to 18.4%) and 19.6% regarding PTSS (13.2 to 28.1%; k = 24). Individuals with cerebrovascular disorder (k = 4) showed the highest pooled point prevalence for PTSD (23.6%, 95% CI, 16.8 to 32.0%), those with cardiovascular diseases the lowest (6.6%, 1.9 to 20.9%; k = 5). The pooled 12-month prevalence of PTSD (k = 3) was 8.8% (95% CI, 5.5 to 13.5%) and the lifetime prevalence (k = 6) was 12.1% (7.6 to 18.5%). Pooled estimates of PTSD prevalence in people with compared to those without CD showed an odds ratio of 9.96 (95% CI, 2.55 to 38.94; k = 5). Conclusion Post-traumatic stress disorder and PTSS are common and substantially higher in people with compared to those without CD. Earlier detection and treatment of this comorbidity might improve mental and physical health, reduce the incidence of further diseases, and reduce mortality. Clinical trial registration https://osf.io/9xvgz, identifier 9xvgz.